Alzheimer disease brain atrophy subtypes are associated with cognition and rate of decline - Risacher, Shannon L. (Neurology, 2017)
OBJECTIVE: To test the hypothesis that cortical and hippocampal volumes, measured in vivo from volumetric MRI (vMRI) scans, could be used to identify variant subtypes of Alzheimer disease (AD) and to prospectively predict the rate of clinical decline. METHODS: Amyloid-positive participants with AD from the Alzheimer’s Disease Neuroimaging Initiative (ADNI) 1 and ADNI2 with baseline MRI scans (n = 229) and 2-year clinical follow-up (n = 100) were included. AD subtypes (hippocampal sparing [HpSp(MRI)], limbic predominant [LP(MRI)], typical AD [tAD(MRI)]) were defined according to an algorithm analogous to one recently proposed for tau neuropathology. Relationships between baseline hippocampal volume to cortical volume ratio (HV:CTV) and clinical variables were examined by both continuous regression and categorical models. RESULTS: When participants were divided categorically, the HpSp(MRI) group showed significantly more AD-like hypometabolism on (18)F-fluorodeoxyglucose-PET (p < 0.05) and poorer baseline executive function (p < 0.001). Other baseline clinical measures did not differ across the 3 groups. Participants with HpSp(MRI) also showed faster subsequent clinical decline than participants with LP(MRI) on the Alzheimer's Disease Assessment Scale, 13-Item Subscale (ADAS-Cog(13)), Mini-Mental State Examination (MMSE), and Functional Assessment Questionnaire (all p < 0.05) and tAD(MRI) on the MMSE and Clinical Dementia Rating Sum of Boxes (CDR-SB) (both p < 0.05). Finally, a larger HV:CTV was associated with poorer baseline executive function and a faster slope of decline in CDR-SB, MMSE, and ADAS-Cog(13) score (p < 0.05). These associations were driven mostly by the amount of cortical rather than hippocampal atrophy. CONCLUSIONS: AD subtypes with phenotypes consistent with those observed with tau neuropathology can be identified in vivo with vMRI. An increased HV:CTV ratio was predictive of faster clinical decline in participants with AD who were clinically indistinguishable at baseline except for a greater dysexecutive presentation.